Analisis Penentuan Tarif Bongkar Muat Peti Kemas Dengan Metode Activity Based Costing (Studi Kasus PT.Pelindo Terminal Petikemas New Makassar) - Nathania Pratiwi; Sahade; Afiah, Nur (Bongaya Journal of Research in Accounting (BJRA), 2023)
This study aims to analyze the determination of container loading and unloading rates using the activity-based costing method at PT PELINDO Terminal Petikemas New Makassar. The variable of this study is the determination of container loading and unloading rates measured using the activity-based costing method. The limits of this research are focused on domestic container loading and unloading rates. This is the case for data collection in the form of observations, interviews and documentation. Data analysis is done by quantitative descriptive analysis. The results of this study show that the calculation of container loading and unloading rates with the activity-based costing method is lower in full 20 feet containers of IDR 116,571.29, full 40 feet of IDR 228,808.74, empty 20 feet of IDR 197,415.69, and empty 40 feet of IDR 204,188.91. Compared with the results of the calculation of container loading and unloading rates carried out by the management of PT PELINDO Terminal Petikemas New Makassar. This is because container loading and unloading rates are calculated by the activity-based costing method based on the type of cost used and various cost drivers.